Visualizing Mathematics: The Use of Block Models for Strategic Problem Solving - Garzon, Julius R; Casinillo, Leomarich F (LPPM Undiksha, 2021)
The ability to visually manipulate problem quantities is often the key to understand effectively the concept towards proper solution process. Modeling blocks in a problem text is a visual mathematical technique that utilizes bar models to express relationship between known and unknown numerical elements. Facing a dismal performance among students entering high school with poor basic problem-solving skills, this study is an attempt to investigate how block model approach potentially reinforce students’ heuristic skills (analytical & procedural) in solving mathematical problems. Two classes of grade 7 students in Ibarra National High School, Maasin City, Philippines were used as participants which is assigned into groups, that is, control and experimental groups. Control group was taught using conventional method while the experimental group was taught using the concept of block model. Using quasi-experimental design, the data analysis revealed significant increase in scores and significant mean difference in problem-solving skills between groups who used and did not use block model method. In conclusion, utilization of block models gives high potential in developing strategic problem-solving ability of learners. Hence, this approach should be incorporated by mathematics teachers in their teaching strategies.